THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE ECONOMY - Nabijonova Saodatkhon Solijon qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article analyzes the positive and negative effects of artificial intelligence (AI) on the economy. It discusses automation, changes in the labor market, emerging economic opportunities, and innovative Al-driven solutions with examples. The article also presents the results of global and local studies and offers policy suggestions.